Penertiban Izin Mendirikan Bangunan (IMB) di Kecamatan Kuta Utara Kabupaten Badung - I Gede Andhika Kusuma Darsana; I Ketut Kasta Arya Wijaya; Luh Putu Suryani (Jurnal Preferensi Hukum, 2021)
Prevention of violations of building construction permits is regulated in a regional regulation where each region has its own power which is called an autonomous region which has an institution in charge of controlling building permits handled by the Civil Service Police Unit. This study aims to determine the authority of local governments in regulating building permits and to analyze law enforcement on buildings that do not have a building permit in North Kuta District, Badung Regency. This study was designed using empirical legal research. The results show that the authority of the local government in controlling building permits aims to regulate the legal relationship between citizens and buildings that are objects of control in order to prevent spatial planning that is not in accordance with the rules. Furthermore, every resident in North Kuta District who owns a building or will build a building is required to have a permit in accordance with the regulations issued by the local government. Then, law enforcement for buildings that do not yet have a Building Construction Permit by providing a warning letter 3 times. If the building owner still ignores the Warning Letter, the Civil Service Police Unit will demolish it according to the Decree from the regional head.